3D versus 2D Systematic Transrectal Ultrasound-Guided Prostate Biopsy: Higher Cancer Detection Rate in Clinical Practice. (25th November 2013) - Peltier, Alexandre; Aoun, Fouad; El-Khoury, Fouad; Hawaux, Eric; Limani, Ksenija; Narahari, Krishna; Sirtaine, Nicolas; van Velthoven, Roland
Abstract : Objectives . To compare prostate cancer detection rates of extended 2D versus 3D biopsies and to further assess the clinical impact of this method in day-to-day practice. Methods . We analyzed the data of a cohort of 220 consecutive patients with no prior history of prostate cancer who underwent an initial prostate biopsy in daily practice due to an abnormal PSA and/or DRE using, respectively, the classical 2D and the new 3D systems. All the biopsies were done by a single experienced operator using the same standardized protocol. Results . There was no significant difference in terms of age, total PSA, or prostate volume between the two groups. However, cancer detection rate was significantly higher using the 3D versus the 2D system, 50% versus 34% (P < 0.05 ). There was no statistically significant difference while comparing the 2 groups in term of nonsignificant cancer detection. Conclusion . There is reasonable evidence demonstrating the superiority of the 3D-guided biopsies in detecting prostate cancers that would have been missed using the 2D extended protocol.